Executive Equity-based Compensation and Managerial Risk-taking Behaviour: A Case Study in the UK Top Banking Institutions - Bun, Rothnita (2022)
Agency theory indicates that including equity in the managerial compensation packages can converge managers’ interest towards the expectation of shareholders, hence they will take more risks to achieve the optimisation of shareholder’s wealth. Even though the correlation between executive compensation and firm risks have been continuously studied by many researchers in the finance field, there is still a controversy regarding their papers. Consequently, the purpose of this paper is to examine the correlation between executive equity-based compensation and firm risks with a case study of thirteen UK major banking institutions. Moreover, the study employs quantitative research methodology using secondary data for a regression analysis. The empirical findings indicate that the correlation between executive equity-based compensation and both total risk and unsystematic risk are insignificantly positive. However, it shows that the independent variable is negatively related to the systematic risk without being significant either. This result, which corresponds with both wealth transfer and risk aversion hypothesis, is consistent with several existing studies. Furthermore, the result also demonstrates significantly positive correlation of firm risks on the equity-based compensation, supporting the information asymmetry theory. In conclusion, the empirical results suggest that executive compensation should be designed with thorough strategies as there is an interrelation between compensation and degree of risk.